RELASI KUASA DAN REPRODUKSI MAKNA RELIGIUSITAS DALAM IKLAN-IKLAN ISLAMI RAMADHAN - Nurus Shalihin (Jurnal Dialog, 2016)
This paper discusses the phenomena of commericals which used Islamic symbols during Ramadhan. The focus of this paper is investigating how the meaning construction occurred in these commercials. The meaning construction mechanism in this study involves: (1) what symbols the commercials use to represent Islam, (2) the relation between Islamic symbols and the marketed products, (3) the situation or context in which the symbols were represented in the commercials, (4) what messages these commercials would like to deliver through Islamic symbols. KEY WORDS: Power relation, meaning production, religiosity, Islamic commercials, consumerism